Digital School Administration Service Systems Addressing Infrastructure And Staff Competency Gaps: Sistem Pelayanan Administrasi Sekolah Digital Mengatasi Kesenjangan Infrastruktur Dan Kompetensi Staf - M Abigil Satria Rifana; Hendra Sukmana; Rossilahi Chasanah; Ashila Mitha Purnamasari; Evi Suryaningsih; Nafisa Kamelia Al Hisyam (Proceedings of The ICECRS, 2025)
General Background Digital information and communication technology provides substantial opportunities for institutional transparency and accountability. Specific Background The transformation of educational workflows in Indonesia faces significant limitations regarding technology access and operational readiness. Knowledge Gap While theoretical frameworks suggest technology adoption guarantees operational efficiency, practical implementation frequently encounters severe hardware deficiencies and personnel resistance. Aims This research investigates the technology utilization workflow at SMAN 1 Krembung to identify existing operational challenges and opportunities. Results The study reveals an average completion time of fifteen minutes and eighty percent user satisfaction; however, technological utilization remains suboptimal due to inadequate hardware, insufficient personnel training, and the absence of platform integration. Novelty This study specifically isolates the discrepancy between high user satisfaction metrics and the underlying systemic technology integration failures in regional educational institutions. Implications Educational policymakers must prioritize targeted personnel technology training, integrated platform development, and sustainable hardware investment to optimize workflows. Highlights: Implementing technology tools cannot guarantee optimal operational efficiency without proper platform integration. User satisfaction reaches eighty percent despite prevailing limitations in institutional hardware resources. Continuous personnel training is essential for navigating technological transitions in educational institutions. Keywords: Educational Management, Information Technology, Platform Integration, Operational Efficiency, User Satisfaction